2017
DOI: 10.4067/s0717-95022017000100012
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Features of the Popliteus Tendon, Popliteofibular and Lateral (Fibular) Collateral Ligaments

Abstract: SUMMARY:To reveal the detailed morphological features of the fibular collateral (fibular) ligament, popliteus tendon, popliteofibular ligament and the synovial components regarding to achieve data for surgical and biomechanical utilization. Knees of 10 formalin-fixed male cadavers were dissected bilaterally. Bursae around the lateral collateral ligament and the relation of popliteus tendon with lateral collateral ligament at the femoral attachment site were noted. The positional relation between both ends of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…This is almost similar to most of the previous studies (15,16). The length of popliteal tendon in present study was found to be shorter than that reported by Kurtoglu et al (17). The mean length and width of the muscle belly was 107.14 mm and 32.38 mm, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…This is almost similar to most of the previous studies (15,16). The length of popliteal tendon in present study was found to be shorter than that reported by Kurtoglu et al (17). The mean length and width of the muscle belly was 107.14 mm and 32.38 mm, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…However, the mediolateral length of popliteus along the lower border was 89.26AE14.41 mm in our study and the width of popliteus at the midpoint was 28.45AE6.85 mm. These dimensions are small in comparison to Kurtoglu et al, 13 may be because of ancestral variations. Hwang et al 14 reported the popliteal length at its lateral border, which was 119AE15 mm.…”
Section: Discussionmentioning
confidence: 57%
“…9 In their study, the distance of distal attachment of popliteus from its musculotendinous junction was 107.14AE13.45 mm and widest part of popliteus measured 32.38AE4.33 mm. Kurtoglu et al 13 reported in their study that popliteus muscle belly length and width were 107.14mm and 32.38mm. However, the mediolateral length of popliteus along the lower border was 89.26AE14.41 mm in our study and the width of popliteus at the midpoint was 28.45AE6.85 mm.…”
Section: Discussionmentioning
confidence: 95%